2022
DOI: 10.3168/jds.2022-22009
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α promotes lipolysis and reduces insulin sensitivity by activating nuclear factor kappa B and c-Jun N-terminal kinase in primary bovine adipocytes

Abstract: Sustained lipolysis and insulin resistance increase the risk of metabolic dysfunction in dairy cows during the transition period. Proinflammatory cytokines are key regulators of adipose tissue metabolism in nonruminants, but biological functions of these molecules in ruminants are not well known. Thus, the objective of this study was to investigate whether tumor necrosis factor-α (TNF-α) could affect insulin sensitivity and lipolysis in bovine adipocytes as well as the underlying mechanisms. Bovine adipocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…A hallmark of an inflammatory state is the release of proinflammatory cytokines, which can result in various metabolic changes, such as anorexia, lipid mobilization, diminished insulin sensitivity, and decreased milk yield ( 88 ). For example, a recent study demonstrated that TNF-α can promote apoptosis, impair insulin sensitivity, and induces a lipolytic response in bovine adipocytes ( 89 ). In addition to playing a role in lipid storage and release, the metabolism of adipose tissue actively regulates homeostasis and the inflammatory response, making it crucial for studying sphingolipid biology ( 90 ).…”
Section: Might Ceramide Play a Role In Immunometabolic Disorders Of T...mentioning
confidence: 99%
“…A hallmark of an inflammatory state is the release of proinflammatory cytokines, which can result in various metabolic changes, such as anorexia, lipid mobilization, diminished insulin sensitivity, and decreased milk yield ( 88 ). For example, a recent study demonstrated that TNF-α can promote apoptosis, impair insulin sensitivity, and induces a lipolytic response in bovine adipocytes ( 89 ). In addition to playing a role in lipid storage and release, the metabolism of adipose tissue actively regulates homeostasis and the inflammatory response, making it crucial for studying sphingolipid biology ( 90 ).…”
Section: Might Ceramide Play a Role In Immunometabolic Disorders Of T...mentioning
confidence: 99%
“…Abnormal FPG concentrations and the risk of insulin resistance related to TNF-α may involve the generation of reactive oxygen species and impairment of insulin signaling through serine phosphorylation, which leads to the development of type 2 diabetes mellitus [ 24 ]. Furthermore, TNF-α promotes lipolysis and reduces insulin sensitivity by activating nuclear factor kappa B and c-Jun N-terminal kinase [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, lipolytic responsiveness wanes after only a few days of sustained stimulation [ 59 , 60 ], and longer periods of stimulation ultimately produce anti-lipolytic effects [ 33 ]. Inflammatory cytokines also stimulate lipolysis [ 61 ], and thus the resolution of greater circulating TNFα and IL-6 in clenbuterol-treated IUGR lambs presumably further reduced circulating NEFA. Additionally, the anti-lipogenic effects of β2 pathways [ 62 ] may explain the concurrent increase of circulating triglycerides observed with clenbuterol, although this was independent of any IUGR effects.…”
Section: Discussionmentioning
confidence: 99%